Effective Removal of Ibuprofen from Aqueous Solution Using Cationic Surface-Active Agents in Dissolved Air-Flotation Process - G. Pooja; P. Senthil Kumar; B. Chitra; Gayathri Rangasamy (International Journal of Chemical Engineering, 2024)
This research paper focuses on the removal of the nonsteroidal anti-inflammatory drug, ibuprofen, from an aqueous solution using a dissolved air flotation process. The comparison of different types of cationic surface-active agents such as cetyltrimethyl ammonium bromide (CTAB), tetrabutyl ammonium bromide (TBAB), and octyltrimethyl ammonium bromide (OTAB) have been employed to scrutinize the effective removal of the ecotoxic pharmaceutically active compound. The work included the influencing parameters such as pressure, contact time, surfactant dosage, pH, flow rate, and initial concentration owing to the best-optimized conditions. The maximum removal rate of 96.09% was achieved at 15 min for CTAB, TBAB had 62.36% at 45 min, and 89.6% was obtained for OTAB at 30 min, with 50 mg L−1 as the initial concentration and pH = 4. The removal rate was better with the optimized dosage of CTAB at 0.6 g, TBAB at 1.2 g, and OTAB at 1.0 g. It was observed that the geometric shape of the surface-active agents had greater impacts on the contaminants’ efficiency. CTAB and OTAB were combined to find out the best possible removal rate of contaminants. The synergistic effect augments surfactant-based occurrence to be better in forming a good foaming effect and tends to have a lower critical micelle concentration (CMC). From the evaluation of kinetic models, pseudo-second-order flotation kinetics fitted the experimental data best. Furthermore, the formed metabolites that had been identified using gas chromatography-mass spectrometry were found to be less toxic than the parenting compounds.